Large-Scale Recombinant Production of the SARS-CoV-2 Proteome for High-Throughput and Structural Biology Applications - Altincekic, Nadide; Korn, Sophie Marianne; Qureshi, Nusrat Shahin; Dujardin, Marie; Ninot-Pedrosa, Martí; Abele, Rupert; Abi Saad, Marie Jose; Alfano, Caterina; Almeida, Fabio C. L.; Alshamleh, Islam; de Amorim, Gisele Cardoso; Anderson, Thomas K.; et al. (Frontiers in Molecular Biosciences, 2021)
The highly infectious disease COVID-19 caused by the Betacoronavirus SARS-CoV-2 poses a severe threat to humanity, and demands for redirection of scientific efforts and criteria to organized research projects. The international Covid19-NMR consortium seeks to provide such new approaches by gathering scientific expertise worldwide. In particular, making available viral proteins and RNAs will pave the way to understanding the SARS-CoV-2 molecular components in detail. The research in Covid19-NMR and the resources provided through the consortium are fully disclosed to accelerate access and exploitation. NMR investigations of the viral molecular components are designated to provide the essential basis for further work, including macromolecular interaction studies and high-throughput drug screening. Here, we present the extensive catalogue of a holistic SARS-CoV-2 protein preparation approach based on the consortium’s collective efforts. We provide protocols for the large-scale production of more than 80% of all SARS-CoV-2 proteins or essential parts of them. Several of the proteins were produced in more than one laboratory, demonstrating the high interoperability between NMR groups worldwide. For the majority of proteins, we can produce isotope-labeled samples of HSQC-grade. Together with several NMR-chemical shift assignments made publicly available on covid19-nmr.com, we here provide highly valuable resources for the production of SARS-CoV-2 proteins in isotope labeled form.